2019
DOI: 10.1097/md.0000000000014067
|View full text |Cite
|
Sign up to set email alerts
|

Top 100 cited articles on infection in orthopaedics

Abstract: Purpose:The infection is an essential problem in the clinical practice in orthopedics. The bibliometric analysis was conducted to evaluate the top 100 cited articles on infection in orthopaedics.Methods:The Web of Science (WoS) Core Database was comprehensively searched from 1975 to 2017, and the literature search was limited in Science Citation Index Expanded (SCI-E). The subject terms included “infection”, “infectious”, and “infect∗”. All retrieved articles were filtrated by selecting the subspecialty of “Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…This finding was in accordance with other previous studies. 19,27 The USA had the highest total citation times. Besides, most productive authors were from the USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was in accordance with other previous studies. 19,27 The USA had the highest total citation times. Besides, most productive authors were from the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that some developing country such as China, Brazil and Chile were selected in rankings, which was entirely different from some other fields, such as infection in orthopedics. 19,27 It should be noted that the two studies from China were not from China mainland, where has the most populations worldwide. Besides, no study was from India, which has the second largest population worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Visualizing the characteristics of data is important and interesting for readers. [ 20 ] Finally, the distinct difference from previous articles [ 10 – 15 ] was that only recent articles collected were included in this study, which improved the relevance and importance for readers.…”
Section: Discussionmentioning
confidence: 99%
“…Although findings are promising based on the above analysis, several potential limitations may encourage further research efforts. First, the study data were only downloaded from PMC, different from other studies [ 10 – 15 ] that used the combination of science Scientific Citation Index (SCI), Scopus, and Google Scholar. Several journals in PubMed have not been indexed by the database of SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation